2020
DOI: 10.1097/ccm.0000000000004236
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Patient Deterioration Using Artificial Intelligence in a Rapid Response System

Abstract: Objectives: As the performance of a conventional track and trigger system in a rapid response system has been unsatisfactory, we developed and implemented an artificial intelligence for predicting in-hospital cardiac arrest, denoted the deep learning-based early warning system. The purpose of this study was to compare the performance of an artificial intelligence-based early warning system with that of conventional methods in a real hospital situation. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 10 publications
1
84
0
Order By: Relevance
“…Our data suggest that systems to improve early identification of deterioration and vital sign changes, including PEWS, may also improve outcomes in these high-risk patients, despite conflicting evidence on the impact of PEWS in general pediatric settings with lower baseline rates of deterioration and mortality (19). Track-andtrigger systems (TTS) based on frequent assessment for and identification of abnormal vital signs in hospitalized children, such as multi-component rule-based systems designed around a scoring tool including vital signs (like PEWS), or more complex machine-learning systems based on the electronic medical record documented vital signs and other clinical data (20)(21)(22), may aid in better identification of patients at risk for deterioration and support clinical decision making around their disposition, particularly in this patient population. Such multi-component systems have consistently been shown to out-perform singleparameter TTS (20,23) at identifying patients with deterioration, and our study suggests these findings hold true in pediatric hematology-oncology patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that systems to improve early identification of deterioration and vital sign changes, including PEWS, may also improve outcomes in these high-risk patients, despite conflicting evidence on the impact of PEWS in general pediatric settings with lower baseline rates of deterioration and mortality (19). Track-andtrigger systems (TTS) based on frequent assessment for and identification of abnormal vital signs in hospitalized children, such as multi-component rule-based systems designed around a scoring tool including vital signs (like PEWS), or more complex machine-learning systems based on the electronic medical record documented vital signs and other clinical data (20)(21)(22), may aid in better identification of patients at risk for deterioration and support clinical decision making around their disposition, particularly in this patient population. Such multi-component systems have consistently been shown to out-perform singleparameter TTS (20,23) at identifying patients with deterioration, and our study suggests these findings hold true in pediatric hematology-oncology patients.…”
Section: Resultsmentioning
confidence: 99%
“…Track-andtrigger systems (TTS) based on frequent assessment for and identification of abnormal vital signs in hospitalized children, such as multi-component rule-based systems designed around a scoring tool including vital signs (like PEWS), or more complex machine-learning systems based on the electronic medical record documented vital signs and other clinical data (20)(21)(22), may aid in better identification of patients at risk for deterioration and support clinical decision making around their disposition, particularly in this patient population. Such multi-component systems have consistently been shown to out-perform singleparameter TTS (20,23) at identifying patients with deterioration, and our study suggests these findings hold true in pediatric hematology-oncology patients. Importantly, such systems must be associated with a robust response algorithm to assure identified abnormal vital signs are appropriately assessed and managed by the medical team.…”
Section: Resultsmentioning
confidence: 99%
“…Horng et al demonstrated that accurate triggering of clinical decision support will become increasingly more important as clinical decision support becomes more integrated into EMRs [27]. Cho et al reported that a deep learning-based early warning system, which can be applied with EMRs, accurately predicted the deterioration of patients [41]. We suggest that our qSOFA-based machine-learning model incorporated with real-time clinical variables on the EMR can be utilized by physicians for making clinical decisions for treating sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Several track and trigger systems (TTSs) using discrete numeric values such as vital signs and laboratory results are used in RRSs [9,10]. As conventional TTSs have limitations in detecting deterioration in patients, several researchers have adopted deep learning based algorithms to deal with these numeric values, which performed better than conventional tools [11][12][13][14][15]. However, the performances of these novel TTSs were also not satisfactory, and further improvement is needed to use the algorithms with electrical health records.…”
Section: Introductionmentioning
confidence: 99%